Pengaruh Senam Kaki Diabetik Menggunakan Koran Terhadap Penurunan Kadar Gula Darah Penderita DM Tipe 2 di Pondok Aren Tangerang Selatan - Ratumas Ratih Puspita; Three Mutmainah (STIKes Kharisma Persada, 2019)
The incidence of diabetes mellitus in Indonesia continues to increase and is one of the most common diseases suffered by the people of Indonesia. Diabetes mellitus is recommended to do diabetes gymnastics. Diabetic foot gymnastic is an activity or exercise conducted by diabetes mellitus patients to prevent injuries and help smooth blood circulation leg. The general objective of this study was to determine the effect of diabetic foot gymnastics by using newspapers against decreased blood sugar levels in patients with type 2 diabetes in Rt.01 / 04 Desa Parigi Lama Pondok Aren Tangerang Selatan. This research uses Quasi Eksperimenal Design (quasi experiment) with one group pretest and posttest approach, that is experiment conducted in one group only without control group. The population in this study was the type 2 diabetes mellitus type 16, the sample amounted to 16 respondents using non probability sampling technique with Incidental sampling technique. The data collection tool is an observation sheet. While the data analysis using Wilcoxon test. Based on data analysis with Wilcoxon analysis test with degree of significance ≤0,05 (5%), the mean of blood sugar level before diabetic foot gymnastics 236,69 mg / dl and after diabetic foot gymnastic is 186,25 mg / dl. The statistical test results show that the value of P value of 0.000 is smaller than the value of α (0.05. This shows that there is Influence of Diabetic Foot Exercise By Using Newsprint Against Reduction Of Blood Sugar Level In Type 2 DM In Rt.01 / 04 Desa Parigi Lama Pondok Aren Tangerang Selatan.